Additively-manufactured monocrystalline YBCO superconductor - Dingchang Zhang; Cristian Boffo; David C. Dunand (Nature Communications, 2025)
Abstract Single-crystal microstructures enable high-performance YBa2Cu3O7-x superconductors which are however limited to simple shapes due to their brittleness. Additive manufacturing can fabricate YBa2Cu3O7-x superconductor with complex shapes, albeit with a polycrystalline microstructure. Here, we demonstrate a route to grow single-crystals from 3D-ink-printed, polycrystalline, sintered superconducting YBa2Cu3O7-x (YBCO or Y123) + Y2BaCuO5 (Y211), manufacturing objects with complex architectures displaying both high critical current density (Jc=2.1 × 104 A.cm–2, 77 K) and high critical temperature (Tc= 88-89.5 K). An ink containing precursor powders (Y2O3, BaCO3, and CuO) is 3D-extruded into complex geometries and then reaction-sintered to obtain polycrystalline Y123 + Y211. A seed is then utilized to transform these 3D-printed parts from polycrystal to monocrystal via the melt growth method. The geometric details of 3D-printed parts survive the process without slumping, sagging or collapse, despite the long-term presence of liquid above the peritectic temperature. Origami structures can be created by sheet folding after 3D-printing. This additive approach enables the facile fabrication of superconducting devices with complex shapes and architectures, such as advanced undulator magnets to generate synchrotron radiation and microwave cavities for dark-matter axion search. This work highlights the potential of additive manufacturing for producing monocrystalline cuprate superconductors and opens the door to additive manufacturing of other monocrystalline functional ceramic or semiconductor materials.